Therapy of CF-Patients with Amitriptyline and Placebo - a Randomised, Double-Blind, Placebo-Controlled Phase IIb Multicenter, Cohort-Study - Lutz Nährlich (Cellular Physiology and Biochemistry, 2013)
Background/Aims: Several recent studies revealed an accumulation of ceramide in bronchial, tracheal and intestinal epithelial cells of mice and patients with cystic fibrosis (CF). Normalization of ceramide concentrations in lungs of CF mice employing the functional acid sphingomyelinase inhibitor amitriptyline also normalized mucociliary clearance, chronic inflammation and infection susceptibility to pulmonary P. aeruginosa in these mice. Methods: To test for a beneficial effect of amitriptyline in vivo, we performed a phase IIb randomised, double-blind, placebo-controlled study. Twenty-one CF patients were treated with 25 mg/d amitriptyline twice daily for 28 days. The placebo consisted of 19 patients and was also treated twice per day. The primary endpoint was the change in lung function in the intention-to-treat (ITT) population. Secondary endpoints were ceramide levels in epithelial cells and safety. Results: After treatment, forced expiratory volume in 1 sec predicted (FEV1) increased 6.3±11.5% (p=0.08) in the ITT population (36 of 40 CF patients) and 8.5±10% (p=0.013) in the per protocol (PP) population (29 of 40 patients). Ceramide levels decreased in nasal epithelial cells after amitriptyline treatment. Amitriptyline had no severe and only mild and mostly transient adverse effects, i.e. xerostomia and tiredness. Conclusion: Amitriptyline is safe in CF-patients, increases FEV1 and reduces ceramide in lung cells of CF patients.